INTERJECTIONS IN SEMARANGAN JAVANESE: A SOCIOPRAGMATIC APPROACH - Nugroho, Raden Arief; Setyaningsih, Nina (HUMANIKA, 2019)
Interjections are widely applied in Javanese dialect and they characterize particular functions, especially in spoken communication. However, with the growth of economic, urbanization, and associated area depopulation, dialect anomaly will lead to two ways: first, a community will be vulnerable as dynamic urbanization occurs; second, its linguistic characteristic will lead to â€œlinguistic salad-bowlâ€ as the result of â€œlinguistic melting-potsâ€. Therefore, it is important to study dialects before they disappear in certain areas.Â In addition, there is relatively little research that has been done on Semarangan Javanese in the area of interjections, as supported by JovanoviÄ‡ (2004), who claims that â€œInterjections, as one of the marginal and perhaps least discussed upon classes of wordsâ€. Semarangan Javanese has some distinct characteristics in its spoken form, especially in its lexical divergence. Consequently, different interjections appear. This research aims to discuss Semarangan Javanese interjections, in terms of the sociopragmatic function applied by Semarangan Javanese speakers in a certain communication context. The researchers applied JovanoviÄ‡â€™s interjections classification as the basis of this research. Field research method was used to gather the data by conducting direct observation to research participants. Semarangan Javanese interjections can be explored into three components, namely form, position, and meaning. Based on the findings, the form of Semarangan Javanese interjections are realized from phonological, morphological, and semantic occurrences. These interjections are also recognized in the initial, final, and independent positions. Such variety of meanings from the interjections can be indicated through several contexts that take place in the communication.